Catalytic Decomposition of HO over Manganese Oxides Supported on an Active Alumina - Nasr-Allah M. Deraz; M.A. El-Sayed; A. Abd. El-Aal (Adsorption Science & Technology)
A series of manganese oxides loaded on to an active alumina support was prepared by impregnation methods and the resulting samples preheated in air at 400°C, 650°C or 900°C for 6 h. The amount of manganese, expressed as Mn 2 O 3 , was varied between 3.7 wt% and 55.3 wt%. The kinetics of the decomposition of H 2 O 2 in an aqueous medium were studied in the presence of these oxides. The catalytic activities increased initially as the amounts of manganese present increased, attaining a maximum value at 13.4 wt% Mn 2 O 3 and then decreasing on increasing both the amount of manganese above this limit and the precalcination temperature from 400°C to 900°C. The specific surface areas of the various catalysts were determined by BET analysis of the nitrogen adsorption isotherms. The S BET values varied from 244 m 2 /g to 80 m 2 /g both as a function of the extent of loading and the precalcination temperature. However, the activation energy for sintering, ΔE S , increased on increasing the amount of Mn 2 O 3 present. The apparent activation energy for H 2 O 2 decomposition conducted over the various solids was found to be virtually unaffected by a change in the amount of manganese present.